2020
DOI: 10.1128/mra.00014-20
|View full text |Cite
|
Sign up to set email alerts
|

Near-Complete Genome Sequence of a Swine Norovirus GII.11 Strain Detected in Japan in 2018

Abstract: Here, we report the near-complete genome sequence of swine norovirus strain SwNoV/Sw1/2018/JP. The genome was genetically similar (90.2%) to that of the only other swine norovirus strain previously detected in Japan (SW/NV/swine43/JP). In conclusion, genome sequences of swine noroviruses in Japan have not been changed significantly in the past 15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Indeed, the information available, although increased over the years, is fragmented, and, most importantly, some studies represent single reports without any follow-up investigations (i.e., studies conducted in Belgium [ 44 ], Slovenia [ 34 ], Spain [ 31 ], Hungary [ 37 ] and Greece [ 45 ], Ethiopia [ 41 ], Taiwan [ 46 ], South Korea [ 32 ], Venezuela [ 47 ]). Only a few countries made more effort in detecting and characterising swine noroviruses, and two or more studies are available for each of these countries (i.e., Italy [ 21 , 22 , 28 , 48 ], USA [ 13 , 20 , 40 , 49 , 50 ], Canada [ 26 , 48 ], China [ 39 , 49 , 50 , 51 ], Japan [ 19 , 20 , 35 , 36 , 52 , 53 , 54 ], Germany [ 33 , 55 ], The Netherlands [ 55 , 56 ], Brazil [ 25 , 29 , 30 , 57 ]). It appears that efforts to investigate the circulation of swine norovirus should be implemented in all continents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the information available, although increased over the years, is fragmented, and, most importantly, some studies represent single reports without any follow-up investigations (i.e., studies conducted in Belgium [ 44 ], Slovenia [ 34 ], Spain [ 31 ], Hungary [ 37 ] and Greece [ 45 ], Ethiopia [ 41 ], Taiwan [ 46 ], South Korea [ 32 ], Venezuela [ 47 ]). Only a few countries made more effort in detecting and characterising swine noroviruses, and two or more studies are available for each of these countries (i.e., Italy [ 21 , 22 , 28 , 48 ], USA [ 13 , 20 , 40 , 49 , 50 ], Canada [ 26 , 48 ], China [ 39 , 49 , 50 , 51 ], Japan [ 19 , 20 , 35 , 36 , 52 , 53 , 54 ], Germany [ 33 , 55 ], The Netherlands [ 55 , 56 ], Brazil [ 25 , 29 , 30 , 57 ]). It appears that efforts to investigate the circulation of swine norovirus should be implemented in all continents.…”
Section: Resultsmentioning
confidence: 99%
“…Due to all the intrinsic limits of the method, ME is no longer used, and only the early studies on swine norovirus reported its use [ 19 , 21 , 22 , 43 , 47 , 58 , 60 ]. In Sugieda et al [ 19 , 54 ], specimens were prepared for EM by cetyltrimethylammonium bromide as described in a previous study [ 53 ], using trihydroxy-dichloro-fluoroethane instead of trichloro-trifluoroethane. In Martinez et al [ 47 ], samples were centrifuged through a 40% ( w / v ) sucrose cushion in PBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation